Tailoring electronic phase separation in Pr-doped mixed-valence manganite (2024)
Mixed-valence manganites are oxides known for their complex phase diagrams. Consequently, they exhibit diverse physical properties, offering multiple degrees of freedom for precise control through various parameters. These include doping, temperature, and external stimuli such as magnetic or electric fields, strain, and pressure. For example, rare-earth manganites doped with calcium can exhibit charge ordering phenomena, metal-to-insulator transitions, and magnetoresistance. The most famous phenomenon is colossal magnetoresistance, where electrical resistance changes by several orders of magnitude with relatively small magnetic fields. One suggested cause of colossal magnetoresistance is phase separation, a phenomenon referring to the coexistence of multiple phases, which has gained significant relevance in current research on mixed-valence manganites. Phase separation emerges due to disorder induced by chemical doping. The separated phases can consist of an antiferromagnetic insulating background coexisting with dispersed ferromagnetic metallic regions. Another case could involve a charge-ordered paramagnetic phase coexisting with disordered regions where ferromagnetic clusters emerge. In other words, a sample of mixed-valence manganite may contain a significant number of coexisting phases that interact with each other. Moreover, some phases can be hidden, which means that in some manganites, the respective complex phase diagram could be incomplete. The interaction between coexisting phases results in exotic physical behaviors that can be exploited in technological applications. However, a complete understanding of phase separation and its control in mixed-valence manganites is still lacking. In this thesis, phase separation in the manganite La5/8−xPrxCa3/8MnO3 (LPCMO) is studied. The existence of hidden phases in this phase-separated system is demonstrated. Additionally, it is shown how the fraction of each coexisting phase can be tailored, allowing control of the electrical resistance as well as the magnetic properties in LPCMO. LPCMO samples with different Pr-doping concentrations were fabricated. The dependence of the phase separation phenomenon on the doping level is studied. The coexistence of antiferromagnetic and ferromagnetic phases is studied through the measurement of magnetic properties. The emergence of a low-temperature paramagnetic phase is revealed using a magnetic resonance method. This dissertation discusses the connection between the reentrance of this paramagnetic phase and glass-like behavior at low temperatures. Magnetic resonance measurements also revealed multiple resonance modes, suggesting the possible presence of hidden phases in LPCMO’s phase separation scheme. Additionally, the magnetic resonance method itself is proposed as a powerful tool for detecting hidden phases in phase-separated systems. Furthermore, this thesis demonstrates that both volatile and non-volatile resistive switching can be induced in LPCMO. Non-volatile resistive switching is achieved by tailoring the fraction of separated phases using electric and magnetic fields. Such tailoring enables the realization of multi-state resistive switching. A possible explanation for the mechanism that allows control of the separated phases is offered in this thesis; measurements of minor temperature loops demonstrate that the evolution of phase separation depends on the sample's thermal history. Consequently, Joule heating caused by electrical pulses can be used to control the fraction of the antiferromagnetic insulating phase. The findings of this thesis provide a new perspective on the phase separation phenomenon in LPCMO. Moreover, the achievement of both volatile and non-volatile resistive switching, along with the ability to perform multi-state resistive switching, highlights the versatility of LPCMO for potential use in next-generation memory devices.